Mutiny on the Boundary? Examining ILK-Based Conservation Collaborations through the Lens of Rubbish Theory - Singleton, Benedict E.; Boyd Gillette, Maris (Ethnobiology Letters, 2023)
Many conservation researchers and practitioners argue that knowledges traditionally conceptualized as non-academic are useful for guiding environmental decision-making and stewardship. As demonstrated by the articles in this special issue, bringing Indigenous and local knowledges to bear on environmental conservation requires forging new relationships and, de facto, new political arrangements. In this article, we seek to clarify what is at stake in such efforts to change (or maintain) what counts as knowledge by applying rubbish theory to the volume’s case studies. Redrawing the boundaries of what counts as conservation knowledge in engagements between academic researchers and practitioners trained to “do conservation” according to western science traditions, on the one hand, and Indigenous peoples and local communities who possess knowledge generated in non-academic contexts, on the other, effects demarcations of expertise and so challenges existing social hierarchies. Unsurprisingly, tension emerges about how far such changes should go. By increasing awareness of the relationship between (re)defining knowledge and (re)configuring social and political hierarchies, we hope to make it easier for participants to manage such collaborations.